2019
DOI: 10.1186/s40659-019-0248-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of JNK and ERK1/2 MAPK signaling pathway in testicular injury of rats induced by di-N-butyl-phthalate (DBP)

Abstract: Background Di- N -butyl-phthalate (DBP) is an endocrine disrupting substance. We investigated the adverse effect of DBP on testis of male rat and reveal its potential mechanism of MAPK signaling pathway involved this effect in vivo and in vitro. Gonadal hormone, sperm quality, morphological change and the activation status of JNK, ERK1/2 and p38 was determined in vivo. Primary Sertoli cell was established and cultivated with JNK, ERK1/2 inhibitors, then determine the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…The reproductive toxicity of these substances has emerged in both animal and cell models [60,61]. There is still debate about the possible mechanisms by which phthalates and/or BPA may damage the male reproductive system, but from the literature, multiple pathways (Nrf2-mediated Notch1 signaling [25], PTEN/AKN pathway [62], ERK1/2 pathway [26]) and multiple target cells might be involved [63]. A structure-activity relationship (SAR) study showed that phthalates with straight side chains (C 4 -C 6 ) have higher male reproduction toxicity, as these phthalates down-regulate the insulin-like peptide 3 (INSL3), involved in the testis descent, and cytochrome P450 11A1 (CYp11a1), causing a lower testosterone production and subsequent reproductive tract anomalies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproductive toxicity of these substances has emerged in both animal and cell models [60,61]. There is still debate about the possible mechanisms by which phthalates and/or BPA may damage the male reproductive system, but from the literature, multiple pathways (Nrf2-mediated Notch1 signaling [25], PTEN/AKN pathway [62], ERK1/2 pathway [26]) and multiple target cells might be involved [63]. A structure-activity relationship (SAR) study showed that phthalates with straight side chains (C 4 -C 6 ) have higher male reproduction toxicity, as these phthalates down-regulate the insulin-like peptide 3 (INSL3), involved in the testis descent, and cytochrome P450 11A1 (CYp11a1), causing a lower testosterone production and subsequent reproductive tract anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The diethylhexylphthalate (DEHP) exposure induced, in rats, testicular toxicity through oxidative stress injury, DEHP levels were linked to the decrement of testosterone levels and upregulated the expression of the nuclear factor-erythroid 2 related factor (Nrf2) [25]. Di-n-butyl phthalate (DnBP) can lead to testicular damage, it impaired the normal structure of testicular tissue, increased sperm abnormality, decrease the viability of Sertoli cells through the activation of extracellular signal regulated kinase 1/2 (ERK1/2) and c-Jun amino terminal kinase (JNK) pathways [26]. To use as a model for human testicular dysgenesis syndrome, pregnant rats were exposed to DnBP and a suppression of intratesticular testosterone, a focal aggregation of Leyding cells and ectopic Sertoli cells were obtained [27].…”
mentioning
confidence: 99%
“…The MAPKs pathway plays important role in regulation of gonadal hormone, sperm quality, morphological change [ 27 ]. To determine the protective effects of GSLS, we measured the expression of MAPK family members, including p-JNK, p-p38 and p-ERK, in the different groups.…”
Section: Resultsmentioning
confidence: 99%
“…MAPK, one of the members of the serine/threonine protein kinase family, is involved in many physiological processes, such as cell proliferation, differentiation and growth, and P38, JNK and ERK, three protein genes in the MAPK pathway, are closely related to oligoasthenozoospermia [ 56 ]. The JNK and ERK1/2 MAPK signaling pathways, which are activated by di-N-butyl-phthalate (DBP), result in testicular injury, thus reducing sperm count by increasing apoptosis [ 57 ]. In addition, the P38 MAPK pathway could be activated by an abnormal arachidonic acid (AA) metabolic network, leading to decreased sperm motility [ 58 ].…”
Section: Discussionmentioning
confidence: 99%